Lithium ion battery electrolyte and application thereof
By introducing additives with specific structures into the lithium-ion battery electrolyte, the mechanical strength and stability of the SEI film are improved, and the battery performance deterioration caused by volume expansion of silicon doped negative electrodes is solved, which significantly improves the cycle life of the battery and maintains the initial performance.
Patent Information
- Application Number
- CN202411988870.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The high-nickel-to-silicon high-energy density system cylindrical lithium-ion battery has a volume expansion of the silicon-doped negative electrode, causing the electrolyte to be squeezed, and the middle part of the coil is partially lean, resulting in damage to the SEI film and an increase in interface impedance, thereby shortening the cycle life of the battery.
A lithium-ion battery electrolyte containing a lithium salt, a solvent and a specific additive is used. The additive includes a compound of the general structure. The electrolyte is used to improve the mechanical strength and stability of the SEI film, inhibit the volume expansion of the silicon-doped negative electrode, and reduce the viscosity of the electrolyte to improve the wettability of the electrode sheet.
It significantly improves the cycle life of lithium-ion batteries, while maintaining the initial impedance and high-temperature storage performance of the battery, extending the service life of the battery.
Smart Images

Figure CN119812471A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art
[0002] As a type of lithium-ion battery, cylindrical batteries have the advantages of high single-cell consistency, good heat dissipation, high production yield and high automation efficiency, and have become the first choice for power batteries for electric vehicles. Among them, the chemical system that matches the high-nickel ternary positive electrode and the silicon-doped graphite negative electrode can compensate for the capacity density of the single cell to ensure the requirements of the cylindrical battery for high energy density and group efficiency. However, in practical applications, due to the volume expansion effect of the silicon-doped graphite negative electrode, on the one hand, the electrolyte is squeezed to the upper and lower ends of the battery column, and the middle section of the pole roll is prone to lithium precipitation due to local poor liquid, resulting in degradation of the battery performance. On the other hand, the solid electrolyte interface (SEI) film is damaged, and in the process of continuous repair and proliferation of the SEI film, the interface impedance increases and the risk of lithium precipitation at the negative electrode is aggravated, which also degrades the battery's cycle capacity. Therefore, for high-nickel-to-silicon high-energy density system cylindrical batteries, short cycle life is the main defect. Summary of the invention
[0003] The present invention proposes a lithium ion battery electrolyte and its application. Through the lithium ion battery electrolyte and its application provided by the present invention, the cycle life of the battery can be significantly improved while ensuring that the initial impedance and high-temperature storage performance of the lithium ion battery are not affected.
[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:
[0005] Lithium salts;
[0006] Solvents; and
[0007] The additive comprises a first additive, and the general structural formula of the first additive is:
[0008]
[0009] Wherein, R1 and R2 are each selected from a C2-C6 unsaturated chain hydrocarbon group.
[0010] In one embodiment of the present invention, R1 and R2 have the same structure, and / or R1 and R2 are C2-C6 alkenyl.
[0011] In one embodiment of the present invention, the first additive is selected from:
[0012] At least one of .
[0013] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.01 wt %-1 wt %.
[0014] In one embodiment of the present invention, the solvent includes a first solvent, the first solvent includes carboxylates, the carboxylates are selected from at least one of methyl acetate, ethyl acetate or ethyl propionate, and the content of the first solvent in the electrolyte is 2wt%-15wt%.
[0015] In one embodiment of the present invention, the solvent also includes a second solvent, which includes cyclic esters and chain esters, the cyclic esters are selected from at least one of ethylene carbonate or propylene carbonate, and the content of the cyclic esters in the electrolyte is 8wt%-24wt%, and the chain esters are selected from at least one of ethyl methyl carbonate or dimethyl carbonate, and the content of the chain esters in the electrolyte is 40wt%-70wt%.
[0016] In one embodiment of the present invention, the lithium salt includes lithium hexafluorophosphate, and the content of the lithium salt in the electrolyte is 14wt%-17wt%.
[0017] In one embodiment of the present invention, the electrolyte further comprises fluoroethylene carbonate, and the content of the fluoroethylene carbonate in the electrolyte is 2wt%-10wt%.
[0018] In one embodiment of the present invention, the additive further includes a second additive, the second additive is selected from at least one of vinylene carbonate, vinyl sulfate, 1,3-propane sultone, lithium difluorooxalate phosphate or lithium difluorooxalate borate, and the content of each of the second additives in the electrolyte is 0.1wt%-1.5wt%.
[0019] The present invention also provides a lithium ion battery, comprising at least:
[0020] A positive electrode sheet, comprising a positive electrode active material, wherein the positive electrode active material has a structural formula of Li x [Ni y Co z Mn t M (1-y-z-t) ]O 2-δ , wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W and Zn, 0.9 <x<1.1,0.9≤y<1.0,0≤z<0.1,0≤t<0.1,0≤δ≤0.1;
[0021] A negative electrode plate, comprising a negative electrode active material, wherein the negative electrode active material is selected from at least one of a graphite-doped silicon-oxygen material and a graphite-doped silicon-carbon material;
[0022] A separator, disposed between the positive electrode sheet and the negative electrode sheet; and
[0023] The electrolyte is selected from the above-mentioned lithium ion battery electrolyte.
[0024] In one embodiment of the present invention, in the negative electrode active material, the doping content of the silicon-oxygen material or the silicon-carbon material is 1 wt %-10 wt %.
[0025] In summary, the present invention proposes a lithium-ion battery electrolyte and its application, which can improve the mechanical strength and stability of the SEI film, inhibit the volume expansion of the silicon-doped negative electrode, reduce the interface impedance degradation and the risk of negative electrode lithium deposition caused by the continuous damage and repair growth of the SEI film, and on the other hand, can effectively reduce the viscosity of the electrolyte, improve the wettability of the electrolyte to the electrode, and reduce the risk of negative electrode lithium deposition. The above two aspects work synchronously to significantly improve the cycle life of the lithium-ion battery. It can also significantly improve the cycle life of the battery while ensuring that the initial impedance and high-temperature storage performance of the battery are not affected. DETAILED DESCRIPTION
[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0027] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0028] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The present invention provides a lithium ion battery electrolyte, which includes at least a lithium salt, a solvent and an additive, wherein the additive includes a first additive, and the first additive has a general structural formula of: Wherein, R1 and R2 are each selected from C2-C6 unsaturated chain hydrocarbon groups. In the lithium ion battery electrolyte provided by the present invention, by introducing the first additive, the mechanical strength and stability of the SEI film can be improved, the volume expansion of the silicon-doped negative electrode can be inhibited, and the interface impedance degradation and the risk of negative electrode lithium deposition caused by continuous damage and repair and proliferation of the SEI film can be reduced, thereby extending the service life of the lithium ion battery.
[0030] In one embodiment of the present invention, the first additive is, for example, a fluorobissulfonamide compound, wherein the structures of R1 and R2 are, for example, the same, and / or, R1 and R2 are, for example, C2-C6 alkenyl. Specifically, in this embodiment, the first additive is, for example, selected from: At least one of. By introducing the first additive, since the functional groups of R1 and R2 have unsaturated bonds, the first additive is easy to undergo a reaction of first adsorption and then polymerization at the negative electrode interface. At the same time, the NF bond in the first additive will be partially broken due to the low bond energy. The partially broken fluoride ions can form LiF inorganic products on the surface of the silicon negative electrode, which helps to form a SEI film interwoven with organic and inorganic components, effectively improve the mechanical strength and stability of the SEI film, and inhibit the volume expansion of the silicon-doped negative electrode during the cycle, thereby reducing the interface impedance degradation and negative electrode lithium plating risks caused by the continuous damage and repair proliferation of the SEI film, thereby improving the cycle life of the battery.
[0031] In one embodiment of the present invention, the content of the first additive in the electrolyte is, for example, 0.01wt%-1wt%, and further, for example, 0.05wt%-0.5wt%. By controlling the content of the first additive, the degree to which the first additive affects the initial impedance of the battery can be alleviated.
[0032] In one embodiment of the present invention, the additive further includes a second additive, and the second additive is selected from at least one of vinylene carbonate (VC), vinyl sulfate (DTD), 1,3-propane sultone (PS), lithium difluoro oxalate phosphate (LiODFP) or lithium difluoro oxalate borate (LiODFB), and the content of each second additive in the electrolyte is, for example, 0.1wt%-1.5wt%. Further, the second additive includes, for example, at least one of VC, LiODFP or LiODFB, and the content of each second additive in the electrolyte is, for example, 0.1wt%-0.5wt%, and the content of each additive in the electrolyte can be equal or unequal. By introducing the second additive into the electrolyte, the composition of the SEI film can be optimized to form a stable and dense SEI film to inhibit the occurrence of side reactions on the electrode surface, increase the initial discharge capacity of the lithium ion battery, improve the high and low temperature storage performance of the lithium ion battery, and improve the high temperature cycle performance of the lithium ion battery.
[0033] In one embodiment of the present invention, the solvent includes a first solvent, and the first solvent includes, for example, carboxylates, and the carboxylates are selected from at least one of methyl acetate (MA), ethyl acetate or ethyl propionate, and the content of the first solvent in the electrolyte is, for example, 2wt%-15wt%, and further, for example, 4wt%-8wt%. By introducing the first solvent of carboxylates, the viscosity of the electrolyte can be effectively reduced, and the conductivity of the electrolyte can be improved, so that the initial impedance of the battery can be effectively reduced. At the same time, when the pressure between the pole coil layers in the middle section of the battery column is high, the electrolyte still has a high wettability to the pole piece, and an effective electrolyte path is maintained, thereby reducing the risk of lithium plating at the negative electrode and further improving the cycle life of the battery. Moreover, the first solvent and the first additive can achieve a complementary effect, and the cycle life of the battery is significantly improved while ensuring that the initial impedance and high temperature storage performance of the battery are not affected. Moreover, by controlling the content of the first solvent, the degree to which the high temperature cycle performance of the battery is affected by the first solvent can be alleviated.
[0034] In one embodiment of the present invention, the solvent further includes a second solvent, the second solvent includes cyclic esters and chain esters, etc. The cyclic esters are selected from at least one of ethylene carbonate (EC) or propylene carbonate, and the content of the cyclic esters in the electrolyte is, for example, 8wt%-24wt%, and the chain esters are selected from at least one of ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC), etc., and the content of the chain esters in the electrolyte is, for example, 40wt%-70wt%. Specifically, in this embodiment, the cyclic esters include EC, the chain esters include EMC and DMC, and the content of EC in the electrolyte is, for example, 16wt%, and the total content of EMC and DMC in the electrolyte is, for example, 43wt%-63wt%. By controlling the content of the second solvent, while exerting the performance of the electrolyte, it is prevented that the second solvent content is too high, resulting in excessive viscosity of the electrolyte, thereby causing problems such as reduced ion conductivity and wettability of the electrolyte.
[0035] In one embodiment of the present invention, the lithium salt includes, for example, lithium hexafluorophosphate (LiPF6), and the content of the lithium salt in the electrolyte is, for example, 14 wt %-17 wt %.
[0036] In one embodiment of the present invention, the electrolyte further includes fluoroethylene carbonate (Fluoroethylene Carbonate, FEC), and the content of FEC in the electrolyte is, for example, 2wt%-10wt%. By adding FEC, FEC forms fluoride ions after decomposition, and the fluoride ions can react with lithium salts in the solvent to produce LiF that is not easy to decompose and has good insulation, which helps to form a uniform, dense, low-impedance and highly elastic SEI film, thereby improving the cycle life of the battery.
[0037] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with a stable gas atmosphere such as argon, after the first solvent and the second solvent are evenly mixed according to a mass ratio, the fully dried lithium salt is added to the above solvent, and the first additive, the second additive and FEC are added to prepare a lithium ion battery electrolyte. The moisture content in the glove box is, for example, less than 10 ppm.
[0038] The present invention also proposes a lithium-ion battery, which is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the lithium-ion battery. The present invention takes a cylindrical battery as an example to illustrate the lithium-ion battery. In this embodiment, the lithium-ion battery includes a shell and a bare cell disposed in the shell, wherein the bare cell includes a positive electrode sheet, a diaphragm, a negative electrode sheet and an electrolyte, the diaphragm is located between the positive electrode sheet and the negative electrode sheet to prevent a short circuit between the positive electrode sheet and the negative electrode sheet, so that lithium ions can pass through, the electrolyte is filled between the positive electrode sheet, the diaphragm and the negative electrode sheet, and the electrolyte is the above-mentioned lithium-ion battery electrolyte, which plays the role of conducting ions.
[0039] In one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0040] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder. The proportion of the positive electrode active material, the conductive agent, and the binder can be selected according to actual needs. In this embodiment, the positive electrode active material is, for example, a high-nickel ternary material, and its chemical formula is, for example, Li x [Ni y Co z Mn t M (1-y-z-t) ]O 2-δ , wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, etc., 0.9 <x<1.1,0.9≤y<1.0,0≤z<0.1,0≤t<0.1,0≤δ≤0.1。
[0041] In one embodiment of the present invention, the conductive agent is, for example, selected from at least one of conductive carbon black (SuperP), acetylene black, carbon nanotubes or graphene, and the binder is, for example, selected from at least one of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR).
[0042] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.9 Mn 0.05 Co 0.05 O2, the conductive agent is, for example, conductive carbon black, and the binder is, for example, polyvinylidene fluoride. The positive electrode active material, the conductive agent and the binder are mixed in a mass ratio of, for example, 97:1:2, dissolved in an organic solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is then evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and a positive electrode sheet is obtained through cold pressing, trimming, cutting and stripping. Among them, the organic solvent is, for example, N-Methylpyrrolidone (NMP).
[0043] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector.
[0044] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener. The proportions of the negative electrode active material, the conductive agent, the binder and the thickener can be selected according to actual needs. In this embodiment, the negative electrode active material is selected from at least one of graphite-doped silicon-oxygen material or graphite-doped silicon-carbon material, wherein the doping content of the silicon-oxygen material or the silicon-carbon material in the negative electrode active material is, for example, 1wt%-10wt%.
[0045] In one embodiment of the present invention, the binder is selected from at least one of PVDF, PEO, PA, polypropylene, polyacrylate, polyvinyl ether, PMMA, polyhexafluoropropylene or SBR, etc. The thickener is selected from at least one of carboxymethyl cellulose sodium (CNC-Na), etc. The conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene, etc.
[0046] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, the negative electrode active material is, for example, graphite-doped silicon oxide material, and the doping content of silicon oxide material in the negative electrode active material is, for example, 3wt%, the doping content of graphite material in the negative electrode active material is, for example, 97wt%, the conductive agent is, for example, conductive carbon black, the thickener is, for example, CNC-Na, and the binder is, for example, SBR. Specifically, the negative electrode active material, the conductive agent, the thickener and the binder carbon are mixed in a mass ratio of 96.5:1:1:1.5, and deionized water solvent is added, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on the copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing, trimming, cutting and stripping.
[0047] In one embodiment of the present invention, the diaphragm is, for example, a conventional diaphragm, a ceramic diaphragm, a polymer diaphragm, a non-woven fabric or an inorganic-organic composite diaphragm, etc. Specifically, the diaphragm is, for example, a single-layer polypropylene (PP) film, a single-layer polyethylene (PE) film, a double-layer PP / PE film, a double-layer PP / PP film or a three-layer PP / PE / PP film, etc. In this embodiment, for example, a single-layer PP film is selected as the diaphragm.
[0048] In one embodiment of the present invention, the positive electrode sheet, separator and negative electrode sheet are placed in sequence, with the separator being located between the positive electrode sheet and the negative electrode sheet to serve as an isolation. A multilayer laminate is obtained by winding and loaded into a battery casing as a bare cell. The lithium-ion battery electrolyte prepared above is then injected into the casing once or multiple times to completely immerse the bare cell in the electrolyte, thereby obtaining a cylindrical battery.
[0049] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0050] Example 1
[0051] Preparation of positive electrode: LiNi 0.9 Mn 0.05 Co 0.05O2, conductive carbon black and polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, dissolved in NMP organic solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain positive electrode slurry. The positive electrode slurry is then evenly coated on aluminum foil, and then transferred to an oven for drying after drying at room temperature. The positive electrode sheet is obtained through processes such as cold pressing, trimming, cutting and slitting.
[0052] Preparation of negative electrode sheet: Silicon oxide material and graphite material are mixed evenly to obtain negative electrode active material, wherein the doping content of silicon oxide material is 3wt% and the doping content of graphite material is 97wt%. The negative electrode active material, conductive carbon black, CNC-Na and SBR are mixed in a mass ratio of 96.5:1:1:1.5, and deionized water solvent is added, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain negative electrode slurry, which is coated on copper foil, and then transferred to an oven for drying after drying at room temperature, and then cold pressed, trimmed, cut and stripped to obtain negative electrode sheet.
[0053] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of less than 1ppm, according to the composition of the electrolyte described in Table 1, the second solvent EC, EMC and DMC are mixed evenly to obtain a solvent, and then the fully dried LiPF6 is added to the solvent, and the first additive compound 1 is added, mixed evenly, and a lithium ion battery electrolyte is prepared. The contents of LiPF6 and compound 1 in the electrolyte are 15wt% and 0.01wt%, respectively.
[0054] Choice of diaphragm: Choose single-layer PP film as the diaphragm.
[0055] Preparation of the battery: The positive electrode sheet, the separator and the negative electrode sheet are placed in sequence, and a multilayer laminate is obtained by winding, and is loaded into a battery casing as a bare cell, and then the electrolyte prepared as above is injected into the casing so that the bare cell is completely immersed in the electrolyte to obtain a cylindrical battery.
[0056] Example 2
[0057] The contents of compound 1 and DMC in the electrolyte were 0.05 wt % and 60.95 wt % respectively. The other steps were the same as those in Example 1.
[0058] Example 3
[0059] The contents of compound 1 and DMC in the electrolyte were 0.2 wt % and 60.8 wt % respectively. The other steps were the same as those in Example 1.
[0060] Example 4
[0061] The contents of compound 1 and DMC in the electrolyte were 0.5 wt % and 60.5 wt % respectively. The other steps were the same as those in Example 1.
[0062] Example 5
[0063] The contents of compound 1 and DMC in the electrolyte were 1 wt % and 60 wt % respectively. The other steps were the same as those in Example 1.
[0064] Example 6
[0065] The electrolyte contains the first solvent MA. The contents of MA, compound 1 and DMC in the electrolyte are 2 wt %, 0.2 wt % and 58.8 wt % respectively. The other steps are the same as those in Example 1.
[0066] Example 7
[0067] The contents of MA and DMC in the electrolyte were 4wt% and 56.8wt% respectively, and the other steps were the same as those in Example 6.
[0068] Example 8
[0069] The contents of MA and DMC in the electrolyte were 8 wt % and 52.8 wt % respectively, and the other steps were the same as those in Example 6.
[0070] Example 9
[0071] The contents of MA and DMC in the electrolyte were 15 wt % and 45.8 wt % respectively, and the other steps were the same as those in Example 6.
[0072] Example 10
[0073] The electrolyte contains FEC, and the contents of FEC, compound 1 and DMC in the electrolyte are 2wt%, 0.2wt% and 58.8wt% respectively. The other steps are the same as those in Example 1.
[0074] Embodiment 11
[0075] The contents of FEC, compound 1 and DMC in the electrolyte were 5wt%, 0.2wt% and 55.8wt%, respectively. The other steps were the same as in Example 10.
[0076] Example 12
[0077] The contents of FEC, compound 1 and DMC in the electrolyte were 10 wt %, 0.2 wt % and 50.8 wt % respectively. The other steps were the same as those in Example 10.
[0078] Embodiment 13
[0079] The electrolyte contains DTD, and the contents of DTD and DMC in the electrolyte are 1 wt % and 59.8 wt % respectively. The other steps are the same as those in Example 3.
[0080] Embodiment 14
[0081] The electrolyte contains MA, FEC, DTD and compound 1 at the same time. The contents of MA, FEC, DTD, compound 1 and DMC in the electrolyte are 8wt%, 5wt%, 1wt%, 0.2wt% and 46.8wt%, respectively. The other steps are the same as Example 1.
[0082] Comparative Example 1
[0083] The contents of compound 1 and DMC in the electrolyte were 0 and 61 wt % respectively. The other steps were the same as those in Example 6.
[0084] Comparative Example 2
[0085] The electrolyte contains MA, and the contents of MA and DMC in the electrolyte are 2 wt % and 59 wt % respectively. Other steps are the same as those in Comparative Example 1.
[0086] Comparative Example 3
[0087] The electrolyte contains FEC, and the contents of FEC and DMC in the electrolyte are 2wt% and 59wt% respectively. Other steps are the same as those in Comparative Example 1.
[0088] Comparative Example 4
[0089] The electrolyte contains DTD, and the contents of DTD and DMC in the electrolyte are 1 wt % and 60 wt % respectively. Other steps are the same as those in Comparative Example 1.
[0090] Comparative Example 5
[0091] The electrolyte contains FN(SO2CH3)2, and the contents of compound 1 and FN(SO2CH3)2 in the electrolyte are 0 and 0.2wt% respectively. The other steps are the same as those in Example 3.
[0092] The raw material component contents and raw material mass ratios required for the electrolytes prepared in the embodiments and comparative examples are shown in Table 1. The content of each component is the mass percentage calculated based on the total mass of the electrolyte.
[0093] Table 1. Composition of the electrolyte in Examples 1-14 and Comparative Examples 1-5
[0094]
[0095] In the present invention, performance tests were performed on lithium-ion batteries prepared using different electrolyte ratios in Examples 1-14 and Comparative Examples 1-5. The test results are shown in Table 2.
[0096] In one embodiment of the present invention, for example, an initial BOL (Beginning of Life) direct current resistance (DCR) test is performed on a lithium-ion battery. Specifically, the temperature of the thermostat is adjusted to 25°C, and the lithium-ion battery is allowed to stand in the thermostat for 10 minutes. Then, the battery is charged to 4.25V at a constant current of 0.33C, and then charged to 0.05C at a constant current at 4.25V. After standing for 30 minutes, the battery is then discharged to 2.5V at a constant current of 0.33C, and allowed to stand for 10 minutes. This cycle is repeated twice to obtain the last discharge capacity C0. The battery is then charged to 4.25V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage. After standing for 30 minutes, the battery is discharged to (50% C0) at a constant current of 0.33C, and allowed to stand for 1 hour. The static terminal voltage V0 is recorded. The battery is then discharged at a constant current of 2C for 10 seconds, and the voltage V1 is recorded. BOL DCR is calculated according to the following formula:
[0097] BOL DCR = (V0-V1) / current value;
[0098] The current value is the current value when the battery is discharged at a constant current of 2C.
[0099] In one embodiment of the present invention, for example, a normal temperature cycle life test is performed on a lithium-ion battery. Specifically, the temperature of the thermostat is adjusted to 25°C, and the lithium-ion battery is stabilized in the thermostat for 30 minutes, and then charged to 4.25V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage, and after standing for 10 minutes, discharged to 2.5V at a constant current of 0.5C, and after 800 cycles of this charge and discharge process, the discharge capacity C1 of the battery cell at the end of the 800th discharge cycle is recorded, and the cycle capacity retention rate of the battery cycled 800 times at 25°C is calculated according to the following formula:
[0100] Cycle capacity retention rate (%) = C1 / C0×100%.
[0101] In one embodiment of the present invention, for example, a high-temperature storage performance test is performed on a lithium-ion battery. Specifically, the temperature of the thermostat is adjusted to 25°C, and the lithium-ion battery is allowed to stand in the thermostat for 10 minutes, and then charged to 4.25V at a constant current of 0.33C, and then charged to 0.05C at a constant current at a voltage of 4.25V. After standing for 30 minutes, it is discharged to 2.5V at a constant current of 0.33C, and then stood for 10 minutes. The cycle is repeated twice, and the last discharge capacity is taken as C2. Then the battery is transferred to a 55°C thermostat and stored for 90 days. Within 90 days, the battery is recharged every 15 days. Specifically, each time the battery is recharged, the battery is transferred to a 25°C thermostat and allowed to stand for 2 hours, and then charged to 4.25V at a constant current of 0.33C, and then charged to 0.05C at a voltage of 4.25V, and then transferred back to a 55°C thermostat for continued storage. After 90 days of storage, the battery was charged and discharged at 0.33C three times, and the last discharge capacity was recorded as C3. The storage capacity retention rate was calculated according to the following formula:
[0102] Storage capacity retention rate = C3 / C2×100%.
[0103] Table 2 Performance test results of lithium ion batteries in Examples 1-14 and Comparative Examples 1-5
[0104]
[0105] Please refer to Table 1 and Table 2. Comparison of Example 3, Comparative Example 1 and Comparative Example 5 shows that when FN(SO2CH3)2 and Compound 1 are compared, when Compound 1 is contained in the electrolyte, the BOL DCR, cycle capacity retention rate and storage capacity retention rate of the battery are significantly increased, and the increase is higher, which shows that the introduction of Compound 1 can effectively improve the stability of the SEI film of the silicon negative electrode, inhibit the volume expansion of the negative electrode and the increase in the internal pressure of the pole coil during the cycle, which causes the local slight lithium precipitation of the negative electrode, thereby effectively improving the cycle life and high-temperature storage performance of the battery. However, the polymerization film of the double bonds in Compound 1 also increases the initial SEI film thickness to a certain extent, resulting in the BOL DCR being affected. Therefore, while Compound 1 improves the cycle life and high-temperature storage performance of the battery, it also affects the initial impedance of the battery.
[0106] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 1-5 that with the increase of the content of Compound 1 in the electrolyte, the BOL DCR, cycle capacity retention rate and storage capacity retention rate of the battery are significantly increased, indicating that: with the increase of the content of Compound 1, although the initial impedance of the battery is affected, the cycle life and high temperature storage performance are significantly improved. Therefore, by controlling the content of Compound 1, the initial impedance, cycle life and high temperature storage performance of the battery can be taken into account.
[0107] Please refer to Table 1 and Table 2. By comparing Comparative Examples 1-2 and Examples 3 and 6, it can be seen that when the electrolyte contains MA, the BOL DCR and storage capacity retention rate of the battery are reduced, and the cycle capacity retention rate increases, which shows that the introduction of MA can effectively reduce the viscosity of the electrolyte and improve the conductivity of the electrolyte, thereby effectively reducing the initial impedance of the battery. At the same time, it can improve the wettability of the electrolyte to the pole piece after the internal pressure of the pole roll increases during the cycle process, maintain an effective electrolyte path, and reduce the risk of local lithium precipitation at the negative electrode, thereby effectively improving the cycle life of the battery. However, due to the poor high-temperature stability of MA itself, the side reaction between MA and the positive electrode interface is aggravated, which affects the high-temperature storage performance of the battery. Therefore, while MA improves the BOL DCR and cycle life of the battery, it also affects the high-temperature storage performance.
[0108] Please refer to Table 1 and Table 2. By comparing Example 3, Example 6 and Comparative Example 1-2, it can be seen that when the electrolyte contains both MA and Compound 1, the BOL DCR of the battery can be achieved without a significant increase, while the cycle capacity retention rate and storage capacity retention rate are significantly increased, indicating that: MA can alleviate the degree to which the initial impedance of the battery is affected by Compound 1, while maintaining the optimization effect of Compound 1 on the cycle life, Compound 1 can alleviate the degree to which the high-temperature storage performance is affected by MA, while maintaining the optimization effect of MA on the cycle life, and MA and Compound 1 work together to further improve the cycle life of the battery. Therefore, MA and Compound 1 can achieve a complementary effect, significantly improving the cycle life of the battery while ensuring that the initial impedance and high-temperature storage performance of the battery are not affected.
[0109] Please refer to Table 1 and Table 2. Comparison of Examples 6-9 shows that as the content of MA in the electrolyte increases, the BOL DCR and storage capacity retention rate of the battery decrease, and the cycle capacity retention rate increases, indicating that: as the content of MA increases, although the initial impedance and cycle life performance of the battery are improved, due to the poor high temperature stability of MA itself, when its content is high, the side reaction between MA and the positive electrode interface is aggravated, resulting in an increase in the loss of battery storage capacity, thereby affecting the high temperature storage performance of the battery. Therefore, by controlling the content of MA, the initial impedance, cycle life and high temperature storage performance of the battery can be taken into account.
[0110] Please refer to Table 1 and Table 2. By comparing Comparative Example 1 and Comparative Example 3, it can be seen that after FEC is introduced into the electrolyte, the BOL DCR and cycle capacity retention rate of the battery increase, and the storage capacity retention rate decreases, which indicates that after FEC is added, it participates in the repair and film formation of the negative electrode SEI, thereby improving the cycle stability and cycle life of the battery, but the initial impedance is affected. At the same time, the introduction of FEC aggravates the acid rise of the high-temperature storage electrolyte, resulting in the high-temperature storage performance of the battery being affected. Therefore, by introducing FEC into the electrolyte, the cycle life of the battery can be improved.
[0111] Please refer to Table 1 and Table 2. By comparing Example 3, Example 10, Comparative Example 1 and Comparative Example 3, it can be seen that when the electrolyte contains both FEC and Compound 1, although the BOL DCR of the battery increases, the cycle capacity retention rate and storage capacity retention rate increase, which shows that: when FEC is used alone, the high temperature storage performance of the battery is affected, but Compound 1 can offset the negative impact of FEC on the high temperature storage performance. At the same time, Compound 1 and FEC work synergistically to further improve the high temperature storage performance, and Compound 1 and FEC work synergistically to further improve the cycle life. Therefore, Compound 1 and FEC work synergistically to further improve the high temperature storage performance and cycle life of the battery.
[0112] Please refer to Table 1 and Table 2. Comparative Examples 10-12 show that as the content of FEC in the electrolyte increases, the BOL DCR and cycle capacity retention rate of the battery increase, and the storage capacity retention rate decreases, indicating that as the FEC content increases, the initial film formation impedance of the battery is affected, and the acid rise of the high-temperature storage electrolyte is aggravated, resulting in the high-temperature storage performance being affected, but the repair effect of FEC on SEI is continuously enhanced during the cycle process, thereby improving the cycle life of the battery. Therefore, by controlling the content of FEC, the cycle life of the battery can be improved without significantly affecting the initial impedance and high-temperature storage performance of the battery.
[0113] Please refer to Table 1 and Table 2. By comparing Comparative Example 1 and Comparative Example 4, it can be seen that after adding DTD to the electrolyte, the BOL DCR of the battery increases slightly, the cycle capacity retention rate remains basically unchanged, and the storage capacity retention rate increases significantly, which shows that DTD participates in strengthening the initial film formation, and the introduction of sulfate inorganic components improves the high temperature stability and the high temperature storage performance of the battery. At the same time, its film-forming organic component is similar to polyethylene oxide (PEO) with good ion conductivity, and the initial film formation impedance is not greatly affected.
[0114] Please refer to Table 1 and Table 2. By comparing Example 3, Example 13, Comparative Example 1 and Comparative Example 4, it can be seen that when the electrolyte contains both DTD and Compound 1, although the BOL DCR of the battery increases, the cycle capacity retention rate is basically the same as the cycle capacity retention rate when the electrolyte contains Compound 1 alone, but the storage capacity retention rate increases significantly, indicating that DTD and Compound 1 work synergistically to further enhance the high temperature stability of the battery and improve the high temperature storage performance of the battery while maintaining the effect of Compound 1 on improving the cycle life. Therefore, DTD and Compound 1 work synergistically to further improve the high temperature storage performance of the battery while improving the cycle life of the battery.
[0115] Please refer to Table 1 and Table 2. By comparing Example 3, Example 8, Example 11, Examples 13-14 and Comparative Example 1, it can be seen that when the electrolyte contains MA, FEC, DTD and Compound 1 at the same time, the BOL DCR of the battery is not large, and the cycle capacity retention rate and the storage capacity retention rate are maintained at a large value, which indicates that when the electrolyte contains MA, FEC, DTD and Compound 1 at the same time, the initial impedance, high temperature storage performance and cycle life of the battery can be comprehensively improved.
[0116] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0117] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. By introducing a first additive into the electrolyte, the mechanical strength and stability of the SEI film can be improved, the volume expansion of the silicon-doped negative electrode can be suppressed, and the interface impedance degradation and the risk of negative electrode lithium plating caused by continuous damage and repair proliferation of the SEI film can be reduced, thereby improving the cycle life of the lithium-ion battery. By introducing a first solvent into the electrolyte, the viscosity of the electrolyte can be effectively reduced, the wettability of the electrolyte to the electrode sheet can be improved, and the risk of negative electrode lithium plating can be reduced, thereby further improving the cycle life of the lithium-ion battery. Moreover, the first additive and the first solvent can achieve a complementary effect, and significantly improve the cycle life of the battery while ensuring that the initial impedance and high-temperature storage performance of the battery are not affected.
[0118] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0119] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Lithium salts; Solvents; as well as The additive comprises a first additive, and the general structural formula of the first additive is: Wherein, R1 and R2 are each selected from a C2-C6 unsaturated chain hydrocarbon group.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: The structures of R1 and R2 are the same, and / or R1 and R2 are C2-C6 alkenyl.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The first additive is selected from: Compound 1 or At least one of compound 2.
4. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.01 wt%-1 wt%.
5. The lithium ion battery electrolyte according to claim 1, characterized in that: The solvent includes a first solvent, the first solvent includes carboxylates, the carboxylates are selected from at least one of methyl acetate, ethyl acetate or ethyl propionate, and the content of the first solvent in the electrolyte is 2wt%-15wt%.
6. The lithium ion battery electrolyte according to claim 5, characterized in that: The solvent also includes a second solvent, which includes cyclic esters and chain esters, the cyclic esters are selected from at least one of ethylene carbonate or propylene carbonate, and the content of the cyclic esters in the electrolyte is 8wt%-24wt%, and the chain esters are selected from at least one of ethyl methyl carbonate or dimethyl carbonate, and the content of the chain esters in the electrolyte is 40wt%-70wt%.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt includes lithium hexafluorophosphate, and the content of the lithium salt in the electrolyte is 14wt%-17wt%.
8. The lithium ion battery electrolyte according to claim 1, characterized in that: The electrolyte further comprises fluoroethylene carbonate, and the content of the fluoroethylene carbonate in the electrolyte is 2wt%-10wt%.
9. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a second additive, which is selected from at least one of vinylene carbonate, vinyl sulfate, 1,3-propane sultone, lithium difluorooxalate phosphate or lithium difluorooxalate borate, and the content of each of the second additives in the electrolyte is 0.1wt%-1.5wt%.
10. A lithium ion battery, characterized in that: include: A positive electrode sheet, comprising a positive electrode active material, wherein the positive electrode active material has a structural formula of Li x [Ni y Co z Mn t M (1-y-z-t) ]O 2-δ , wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W and Zn, 0.9 <x<1.1,0.9≤y<1.0,0≤z<0.1,0≤t<0.1,0≤δ≤0.1; A negative electrode plate, comprising a negative electrode active material, wherein the negative electrode active material is selected from at least one of a graphite-doped silicon-oxygen material and a graphite-doped silicon-carbon material; A separator, disposed between the positive electrode sheet and the negative electrode sheet; and An electrolyte, wherein the electrolyte is selected from the lithium ion battery electrolyte according to any one of claims 1 to 9.
11. The lithium ion battery according to claim 10, characterized in that: In the negative electrode active material, the doping content of the silicon-oxygen material or the silicon-carbon material is 1 wt %-10 wt %.
Citation Information
Patent Citations
High-voltage electrolyte for lithium battery
CN114142088A
Electrolyte and battery
CN116706241A
Electrolyte and battery using it
CN1622386A
Lithium ion secondary battery
KR1020060015907A